Pests and Vector-Borne Diseases in the Livestock Industry 2018
DOI: 10.3920/978-90-8686-863-6_11
|View full text |Cite
|
Sign up to set email alerts
|

11. Biological control with parasitoids

Abstract: Worldwide the livestock industry, from small farmers to large industrialized farms, is affected by arthropods and arthropod-borne diseases at various scales, which cause huge losses and are a constraint to socio-economic development. Farmers make considerable efforts to prevent and control pest and disease incidence, often requiring the use of vaccines, if available, drugs and pesticides. Examples of current problems are presented, to set the stage for the detailed and state-of-the-art presentations of specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 210 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…It is estimated that stable flies can cost the livestock industry $2.2 billion per year. Parasitoid wasp species in the genus of Muscidifurax are excellent biological control agents for dipteran filth flies, including house fly, stable fly, Frontiers in Microbiology frontiersin.org horn fly, black dump fly, and flesh fly (Petersen and Currey, 1996;Geden and Hogsette, 2006;Geden and Moon, 2009;Machtinger and Geden, 2018). These parasitoids are more environment-friendly and sustainable, and host flies are not known to develop resistance to them, as they do with chemical insecticides (Oyarzun et al, 2008;Scott et al, 2013).…”
Section: Toward An Ultimate Cure For Nosemosismentioning
confidence: 99%
“…It is estimated that stable flies can cost the livestock industry $2.2 billion per year. Parasitoid wasp species in the genus of Muscidifurax are excellent biological control agents for dipteran filth flies, including house fly, stable fly, Frontiers in Microbiology frontiersin.org horn fly, black dump fly, and flesh fly (Petersen and Currey, 1996;Geden and Hogsette, 2006;Geden and Moon, 2009;Machtinger and Geden, 2018). These parasitoids are more environment-friendly and sustainable, and host flies are not known to develop resistance to them, as they do with chemical insecticides (Oyarzun et al, 2008;Scott et al, 2013).…”
Section: Toward An Ultimate Cure For Nosemosismentioning
confidence: 99%
“…Several biological control options are available for the control of house flies. Parasitoid wasps, generally in the genera Muscidifurax and Spalangia (Hymenoptera: Pteromalidae), have been used for fly control (Machtinger and Geden 2018). These parasitoids kill the pupal stage of the developing fly: and while they occur naturally in low numbers, several species can be purchased commercially as part of an augmentative biological control program.…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory and field studies have indicated that tephritoid flies are susceptible to several pteromalid pupal parasitoids that also commonly attack "filth flies" such as house flies and stable flies [15][16][17]. These parasitoids, mostly in the genera Muscidifurax, Spalangia, and Nasonia, have a wide host range and similar life histories [18]. Female parasitoids deposit venom and either a single egg (solitary species such as Muscidifurax raptor, Muscidifurax zaraptor and Spalangia spp.)…”
Section: Introductionmentioning
confidence: 99%
“…Pupation occurs within the host puparium and adults emerge by chewing and escaping through an emergence hole after ca. 14-28 days at 27 • C, depending on the species [18].…”
Section: Introductionmentioning
confidence: 99%